Study the Impact of Banking Management Choices on Disclosing Future Profits and the Impact of Bank Characteristics on Management Choices - KAREEM, AHLAM HAMEED; Mabrouk, Houda Ben (Journal of Ecohumanism, 2024)
As we are in the process of keeping pace with globalization and challenging global markets, attention must be paid to two important aspects, the first of which is attention to practical activities and the second of which is adequate accounting disclosure in the financial reports and providing them to the concerned authorities and stakeholders inside and outside the company, and placing this disclosure within a framework with which the financial reports in companies can be compared, This study aims to uncover and measure earnings management practices in the Iraqi banking environment, and attempt to measure earnings management practices. To achieve this goal, a sample of fifteen Iraqi banks listed on the stock market and stock exchange was used for the period (2010 - 2020), The study tested the impact of earnings management practices using the modified Jones model on future profits and the operating cash flows that make up current profits. The modified Jones model (Jones: 1991) is one of the models used to measure earnings management through the use of a regression model to measure optional accruals. Several hypotheses were used for the study: The effect of optional dues on future profits, The larger the bank, the greater the impact of receivables on future profits., The greater the bank’s debt ratio, the greater the impact of optional receivables on future profits, The greater the ratio of the market value to the book value of the bank’s shares, the greater the impact of optional dues on future profits, The greater the bank’s revenue growth, the greater the impact of optional accruals on future profits, The greater the deviation in the bank’s operational activity, the greater the impact of optional accruals on future profits, This study reached important results, including: There is a positive relationship between optional entitlements and future levels of profits. Optional benefits are the least sustainable component of current profits in the future.